Neutral description and exchange of design computational workflows - Gondhalekar, A. C.; Guenov, Marin D.; Wenzel, H.; Nunez, M.; Balachandran, L. K. (The Design Society, 2011)
Proposed in this paper is a neutral representation of design computational workflows which allows their exchange and sharing between different project partners and across design stages. This is achieved by the de-coupling of configuration and execution logic. Thus, the same underlying workflow can be executed with different (fidelity) models and different software tools as long as the inputs and outputs of the constituent process are kept the same. To this purpose, an object model is proposed to define different simulation objects, their scope, and hierarchy in the simulation process. An XML based computer readable representation of workflows based on the proposed object model, is also suggested. The application of the proposed representation is demonstrated via a case study involving the exchange of workflows between two design partners. The case study also demonstrates how the same workflow can be executed using different execution tools and involving different fidelity models.
Keywords: Computational workflows; data/information sharing; model-based design